Is your graduate nurse suffering from transition shock? - Erin Wakefield (Journal of Perioperative Nursing)
The term ‘transition shock’ is a relatively new concept used to describe the experience of moving from the comfortable and familiar role of the preregistration nursing student to the professional registered nurse (RN). The initial and most dramatic stage in this theory of role adaption occurs over the first four months of professional practice.